2015
DOI: 10.1039/c5ra11131e
|View full text |Cite
|
Sign up to set email alerts
|

Glutaraldehyde sandwiched amino functionalized polymer based aptasensor for the determination and quantification of chloramphenicol

Abstract: In the present work, the crosslinking property of glutaraldehyde (GA) is exploited to construct a 1,5-diaminonaphthalene (1,5-DAN) modified aptamer based sensor for the determination and quantification of chloramphenicol (CAP). The sensor was fabricated by electro-polymerizing 1,5-DAN on the edge plane pyrolytic graphite (EPPG) followed by immobilization of CAP selective aptamer on the amino functionalized polymer modified EPPG surface using GA, which resulted in covalent linkage with the -NH 2 groups of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Mehta et al [147] identified and investigated the ssDNA aptamer sequence which was later used in numerous studies dealing with the aptasensing of chloramphenicol. The lowest LOD could be obtained by Chen et al [173], followed by Rosy et al [169] using amperometric aptasensors. The structure of quinolone is marked red.…”
Section: Chloramphenicolmentioning
confidence: 95%
See 1 more Smart Citation
“…Mehta et al [147] identified and investigated the ssDNA aptamer sequence which was later used in numerous studies dealing with the aptasensing of chloramphenicol. The lowest LOD could be obtained by Chen et al [173], followed by Rosy et al [169] using amperometric aptasensors. The structure of quinolone is marked red.…”
Section: Chloramphenicolmentioning
confidence: 95%
“…The presented aptasensor of Yadav et al [166] was further developed by Rosy et al [169], exploiting the cross linking properties of glutaraldehyde (GA). For sensor fabrication, first 1,5diamoinonaphtalene was linked to the working electrode, consisting of edge plane pyrolytic graphite (EPPG), via electro-polymerization.…”
Section: Chloramphenicolmentioning
confidence: 99%
“…Like the other antibiotics, there are more reports of constructed electrochemical aptasensors for the detection of chloramphenicol [ 41 , 49 , 112 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 ] As shown in Table 9 , the lowest LOD could be obtained using the proposed electrochemical aptasensor based on Y-shaped DNA probes [ 174 ]. These probe-based metal ions encoded the nanoscale metal-organic frameworks (NMOF) as a substrate, and a circular strand-replacement DNA polymerization (CSRP) target triggered the amplification strategy.…”
Section: Aptasensors For Different Antibiotic Classesmentioning
confidence: 99%
“…The articles on electrochemical aptasensors cited in Table correspond to reports in which conformational changes are defined (or assumed) to explain the way the devices work. There are other reports in which the conformation is just mentioned, but not defined in detail. ,, It can be observed that gold, including its nanoparticles (AuNPs), constitutes the surface that has been mainly used to associate the selected aptamer containing a thiol group, either directly tethered (−SH) or, more commonly, through a spacer arm containing that same terminal group.…”
Section: Aptamersmentioning
confidence: 99%